Optimalisasi Pembelajaran Bahasa di SD: Peran RPP dan Modul Ajar dalam Pembelajaran Sastra - Yudianto, Asep (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2024)
This study aims to analyze the implementation of the Lesson Implementation Plan (RPP) and Teaching Module in literature learning in Elementary Schools (SD), and its impact on students' language skills. This study uses a qualitative approach with a literature analysis method to examine the implementation of RPP and Teaching Module in literature learning. Data were collected through a systematic review of various relevant literature, such as journal articles, books, research reports, and other documents that discuss the learning process in elementary school classes that have implemented RPP and Teaching Module. The data collection process was carried out by identifying literature sources based on topic relevance, publication quality, and relevance to the implementation of RPP and Teaching Module. Document analysis was conducted to explore the use of RPP and Teaching Module in literature learning, with a focus on implementation strategies, effectiveness, and challenges faced. The results of the study indicate that RPP plays an important role in providing a clear framework for teachers, while Teaching Module is effective in increasing students' interest and language skills. The combination of the two creates a varied and interesting learning environment, enriches students' language skills, and fosters appreciation for literature. Recommendations proposed include ongoing teacher training and the development of more contextual learning materials and the use of technology to improve the quality of language learning in elementary schools.   Abstrak Penelitian ini bertujuan untuk menganalisis implementasi Rencana Pelaksanaan Pembelajaran (RPP) dan Modul Ajar dalam pembelajaran sastra di Sekolah Dasar (SD), serta dampaknya terhadap keterampilan berbahasa siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis literatur untuk mengkaji penerapan RPP dan Modul Ajar dalam pembelajaran sastra. Data dikumpulkan melalui tinjauan sistematis terhadap berbagai literatur yang relevan, seperti artikel jurnal, buku, laporan penelitian, dan dokumen lainnya yang membahas proses pembelajaran di kelas SD yang telah menerapkan RPP dan Modul Ajar. Proses pengumpulan data dilakukan dengan mengidentifikasi sumber literatur berdasarkan relevansi topik, kualitas publikasi, dan keterkaitan dengan implementasi RPP dan Modul Ajar. Analisis dokumen dilakukan untuk mengeksplorasi penggunaan RPP dan Modul Ajar dalam pembelajaran sastra, dengan fokus pada strategi implementasi, efektivitas, dan tantangan yang dihadapi. Hasil penelitian menunjukkan bahwa RPP berperan penting dalam memberikan kerangka kerja yang jelas bagi guru, sementara Modul Ajar efektif dalam meningkatkan minat dan keterampilan bahasa siswa. Kombinasi keduanya menciptakan lingkungan pembelajaran yang variatif dan menarik, memperkaya keterampilan berbahasa siswa, serta menumbuhkan apresiasi terhadap sastra. Rekomendasi yang diajukan meliputi pelatihan guru berkelanjutan dan pengembangan materi pembelajaran yang lebih kontekstual serta pemanfaatan teknologi untuk meningkatkan kualitas pembelajaran bahasa di SD.